Reconstruction Draft Testing Regulation Legislation in System Law National : Study Theoretical and Legal to Function Testing in Ensure Supremacy Constitution - Wicipto Setiadi; Kaharuddin Kaharuddin; Evi Fitriani; Dimas Yanuarsyah (Badan Penerbit STIEPARI Press, 2024)
This article discusses the urgency of reconstructing the concept and mechanism of reviewing legislation in the Indonesian national legal system. The main focus is on the dualism of authority between the Constitutional Court and the Supreme Court, weak public participation, and lack of transparency in the judicial review process. Using a normative approach based on Hans Kelsen's hierarchy of norms theory and Satjipto Rahardjo's progressive law, this study highlights the need for a testing system that is not only legal-formal but also substantive and fair. Findings indicate that the separation of authority without coordination leads to inefficiency, inconsistent decisions, and a crisis of legal legitimacy. A comparative study of systems in Germany, South Korea, and the United States serves as the basis for developing an ideal model of judicial review that is centralized, transparent, participatory, and responsive to constitutional values. This research recommends institutional reforms, the development of integrated procedural standards, the digitization of the judicial review system, and the establishment of a unit to oversee the implementation of decisions. As a result, judicial review can function optimally as a corrective tool against unconstitutional regulations and ensure the supremacy of the constitution in Indonesia's constitutional practice.